2018
DOI: 10.4315/0362-028x.jfp-17-318
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella during Production of Partially Sprouted Pumpkin, Sunflower, and Chia Seeds Dried for Direct Consumption

Abstract: Ready-to-eat foods based on dried partially sprouted seeds have been associated with foodborne salmonellosis. Whereas research has focused on the potential for Salmonella initially present in or on seeds to grow and survive during fresh sprout production, little is known about the potential for growth and survival of Salmonella associated with seeds that have been partially sprouted and dried. The goal of this study was to determine the growth of Salmonella during soaking for partial germination of pumpkin, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…1C). Final cell densities were comparable to those previously reported for soaked pumpkin, sunflower, and chia seeds (14).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1C). Final cell densities were comparable to those previously reported for soaked pumpkin, sunflower, and chia seeds (14).…”
Section: Resultssupporting
confidence: 88%
“…), will influence the lag time and the growth rate of Salmonella. Keller et al (14) reported average lag times of 3.45 h (sunflower) to 6.68 h (chia) during soaking at 25°C; however, these times were highly variable between replicates (standard deviations averaging 2 h). Shortening the soaking time to < 3 h to mitigate the potential growth of Salmonella is not a viable option because many of these commodities would not be fully hydrated in this time frame.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…to survive on these foods (nuts, black pepper, and spices) in a low-moisture environment. Numerous studies on the survival of Salmonella enterica in dried foods have previously been published (13) using a cocktail of different strains. Here, we report the complete closed genome sequences of 5 strains commonly used in these studies, S.…”
Section: Announcementmentioning
confidence: 99%
“…However, higher values of Salmonella prevail in sesame (12%) and chia (31%) were detected by Arana et al [14] . In 2014, a chia seed meal was associated with an outbreak of Salmonella , which involved 63 cases recorded in Canada and 31 in the United States [15] . In addition, in the United States, several edible seeds, such as chia, sunflower and pumpkin seeds, have been subjected to multiple recalls from the market due to the presence of Salmonella [15] .…”
Section: Introductionmentioning
confidence: 99%